Analysis Of Perception And Motivation Of Passengers Using Kualanamu International Airport With Service Innovation As A Mediating Variable - Faisal hakim; Mesra B; Elfitra Desy Surya (International Journal of Management, Economic and Accounting, 2024)
This research aims to determine and analyze perceptions, motivation and have a positive and significant influence on passengers' decisions to use Kualanamu International Airport mediated by service innovation. This type of research is quantitative descriptive research using Partial Least Squares- Structural Equation Modeling (PLS-SEM) data analysis. The data source comes from a questionnaire. The population in this study was all passengers at Kualanamu International Airport. The sampling technique used random sampling technique, the number of samples in the study was 150 passengers. The results of the analysis show that consumer perception has a positive and significant effect on passengers' decisions to use Kualanamu International Airport, consumer motivation has a positive and significant effect on passengers' decisions to use Kualanamu International Airport. The relationship is not shown in the consumer perception variable which has a positive and significant influence on Kualanamu International Airport passenger decisions mediated by service innovation. Consumer motivation variables have a positive and significant effect on Kualanamu International Airport passenger decisions mediated by service innovation.